Food Safety as Culinary Infrastructure in Singapore, 1920–1990. Issue 2 (2nd July 2016) - Tarulevicz, Nicole
Abstract: A nuanced understanding of food safety encompasses how people think about food threats and safety and the interwoven institutions, regulations, and technologies that create the related knowledge. Using examples drawn from Singapore, this article shows that the less structured, more informal body of popular knowledge about food safety can be understood as a kind of culinary infrastructure. In a nation that has always relied on imported food, a contextual and contingent historical approach demonstrates elements of continuity and change in popular food safety knowledge, across colonial and postcolonial moments. A complex tripartite arrangement among the main local players – the state, merchants, and the consumers – was established which emphasized local responsibility for food safety. This is illustrated by the commercial and information functions of the local English-language press, where articles, advertising campaigns for products such as refrigerators and insecticide, public campaigns, and consumer advocates helped shape knowledge of food safety as a shared responsibility. Singapore's experience highlights popular knowledge as culinary infrastructure and is relevant for a globalized world, demonstrating a food safety regime geographically distant from food production and simultaneously highly reliant on effective local actors. In so doing, Singapore suggests a potential alternative way to engage with globalized food – via a popular focus on shared local responsibilities.